1977
DOI: 10.1051/rnd:19770409
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin secretion in infertile men before and after treatment with bromocriptine

Abstract: Summary. This report studies prolactin secretion in infertile men and the effect of bromocriptine treatment.Twelve

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1980
1980
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…Our data provide the first demonstration that as a whole neither basal prolactin levels nor its response to sulpiride were altered in varicocele patients. The literature reports hyperprolactinemia in infertile men, mainly in cases of severe oligozoospermia (Boucher et al -1977); we could not verify this relationship in our series, since the mean spermatozoa count in our patients was 19.1 million per ml. tion of testis.…”
Section: Discussioncontrasting
confidence: 70%
“…Our data provide the first demonstration that as a whole neither basal prolactin levels nor its response to sulpiride were altered in varicocele patients. The literature reports hyperprolactinemia in infertile men, mainly in cases of severe oligozoospermia (Boucher et al -1977); we could not verify this relationship in our series, since the mean spermatozoa count in our patients was 19.1 million per ml. tion of testis.…”
Section: Discussioncontrasting
confidence: 70%
“…Some studies suggest that PRL may normally act to stimulate steroidogenesis (Ambrosi et al -1976;Rubin et al -1976;Boucher et al -1077a). Others, however, indicate an inhibitory effect of hyperprolactinemia (Besser and Thorner -1075;Magrini et al -1976;Boucher et al -1977a). Our results suggest PRL increase resulting from spermatogenesis and/or Leydig cell damage.…”
Section: Discussionmentioning
confidence: 39%
“…Boucher et al studied the effects of bromocriptine in individuals with hyperprolactinemia and demonstrated that the prolactin secretion was lowered and spermatogenesis which was altered was restored back to normal [33]. Another study by Merino et al showed high levels of prolactin in patients with different infertile conditions like oligozoospermia, asthenozoospermia and azoospermia [34].…”
Section: Prolactin and Its Receptor Knockoutsmentioning
confidence: 99%